Bruner’s theory on the development of e-book traditional snacks ethnomathematics for mathematical understanding ability - Rani Darmayanti; Dwi Priyo Utomo; Choirudin Choirudin; Usmiyatun Usmiyatun; Phong Thanh Nguyen (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2023)
This study aims to make traditional books that were packaged electronically with an ethnomathematics approach to traditional snacks, which was adapted from Bruner's theory by presenting three stages of Bruner's theory as enactive, iconic, and symbolic by incorporating elements of traditional snacks as an ethnomathematics approach as an effort to build students' mathematical understanding abilities. The method used the 4-D concept by using questionnaires and test instruments so that this media was valid and suitable for use as a medium in learning mathematics. The results showed a score of 3.86 for material experts and 3.74 for media experts, with 82% eligibility criteria to improve students' mathematical understanding abilities. The response to the ethnomathematics-based e-book was 91% with the "Very Eligible" criteria. It can be concluded that this e-book was developed to meet valid criteria and is practical and effective in use.